PROCESSING AND UTILIZATION OF PUMICE AS AN ALTERNATIVE MIXTURE IN MAKING CONCRETE BRICKS (PAVING BLOCKS) TO INCREASE COMMUNITY INCOME - Muhammad; Ichsan Rusydi; Syamsul Rizal; Zulfan; Muhammad Syukri; Thaib Rizwan; Zulkarnain Jalil; Razali Thaib (Jurnal Pengabdian Bangsa, 2023)
Aceh Besar Regency, in this case Mesjid Raya District, is an area that has quite promising geological conditions, both in terms of the type and distribution of rocks. This makes it possible for many mining excavations that have high economic value to be found in this area. However, the utilization of these mining materials has not been optimized until now. One type of mining material in question is pumice. This pumice is found in large quantities in Paya Kameng village. However, so far the people in this village have only used it as additional building materials without any effort to increase its benefits. Therefore, it was tried to use it for raw materials in the industrial and construction sectors such as in the manufacture of concrete bricks. Concrete bricks (paving blocks) are a type of non-structural concrete that can be used for roads, parking lots, sidewalks, parks and other needs. Concrete bricks are made from a mixture of type I portland cement and water and aggregates as fillers. Aggregates or fillers occupy 75% of the total volume of concrete, so that the properties of the aggregates have a major influence on the behavior of hardened concrete. The aggregate that is often used is sand.